Quantitative prediction of rare earth concentrations in salt matrices using laser-induced breakdown spectroscopy for application to molten salt reactors and pyroprocessing. Issue 1 (10th November 2020) - Hull, Gregory; Lambert, Hugues; Haroon, Kiran; Coffey, Paul; Kerry, Timothy; McNaghten, Edward D.; Sharrad, Clint A.; Martin, Philip
Abstract : Pyroprocessing of spent nuclear fuels is an electrochemical separation method where spent metallic fuel is dissolved in a molten salt bath to allow uranium (U) and plutonium (Pu) to be isolated from fission products (FPs) and other impurities. Abstract : Pyroprocessing of spent nuclear fuels is an electrochemical separation method where spent metallic fuel is dissolved in a molten salt bath to allow uranium (U) and plutonium (Pu) to be isolated from fission products (FPs) and other impurities. This allows the useful materials to be reused in mixed oxide fuel (MO x ) or further refined to new reactor fuel. Monitoring the changing concentrations of U, Pu, FPs and other species inside a molten salt vessel presents a unique challenge which laser-induced breakdown spectroscopy (LIBS) may be able to overcome, due to its ability to simultaneously analyse multiple elements using a single measurement with stand-off capability in situ . In this study, samples of praseodymium (Pr), holmium (Ho) and erbium (Er) chloride (LnCl3 ) in LiCl + KCl eutectic (LKE) salt were analysed with LIBS. Multiple laser pulse energies were tested to maximise the signal to background ratio, the best results were obtained at the lowest pulse energy of 85 mJ per pulse. Forward interval Partial Least Squares (iPLS) regression was used to create predicted versus measured concentration models for each element. This method achieved Root Mean Squared Error of Cross Validation (RMSECV) values of between 3.20 × 10 −3 and 16.3 × 10 −3 mmolLn gLKE −1 for single lanthanide samples and 2.84 × 10 −3 and 7.62 × 10 −3 mmolLn gLKE −1 for mixed samples of all three lanthanide elements. Limits of quantification of between 1000 and 9000 ppm suggest LIBS should be a candidate for on-line analysis of elemental concentrations during pyroprocessing.